TRADISI PRAJANJEN: EKSISTENSI NILAI KESETARAAN GENDER DALAM ADAT PERKAWINAN PADA MASYARAKAT DESA EROMOKO KECAMATAN EROMOKO KABUPATEN WONOGIRI - Ridho, Muhammad Rosyid; Khasanah, Uswatul (Inisiasi, 2025)
One area that is unique in this proposal process is in Eromoko Village, Eromoko District, Wonogiri Regency. In this village there is a custom of proposing marriage called prajanjen. This custom of proposing marriage is a tradition that has been passed down from generation to generation in Eromoko which requires the prospective bride and groom to make and sign a letter of agreement. Seeing the uniqueness of the tradition, the purpose of this study is (1) to examine the implementation of the prajanjen tradition in Eromoko Village and (2) to analyze gender equality in the implementation of the prajanjen tradition in Eromoko Village. The research method used is qualitative descriptive. The location of the study was in Eromoko Village, Eromoko District, Wonogiri Regency. Research data was collected using in-depth interview techniques. After the data was collected, data analysis was carried out using a gender approach. The results of this study are, first, prajanjen is an agreement between the two parties, but in general it contains sanctions or fines that must be paid for those who cancel in advance. If in the form of a fine, then the fine will be given to the injured party, namely the prospective bride and groom and the village which will then be used as village cash funds. However, this prajenjen is only applied to those who will get married within the next six months or one year. Furthermore, the principle of gender equality has been manifested in the prajanjen tradition as has been carried out by the residents of Eromoko Village. In fact, this tradition can be the identity of Eromoko residents in terms of protecting the rights of its citizens, especially in terms of marriage.